Accurate prediction of the 2022 M S 6.9 Menyuan and M S 6.8 Luding earthquake epicentres - Yiqing Zhu; Xiong Yang; Yunfeng Zhao; ShouChun Wei; Guoqing Zhang; Fang Liu (Scientific Reports)
Abstract In 2022, the M S 6.9 Menyuan (Qinghai Province) and M S 6.8 Luding (Sichuan Province) earthquakes occurred successively on China’s North–South seismic belt. Both earthquakes caused serious property losses, and the Luding earthquake caused 100 + casualties. Gravity observations performed in the North–South Seismic Belt before the two earthquakes indicate that gravity changes occurred near the epicentres and exhibited four-quadrant distributions. In this study, We reviewed the successful prediction of these two earthquakes by using gravity data. The distances between the actual and predicted epicenters of the two earthquakes were < 56 km in 2022 and < 10 km in 2021. Before both earthquakes, gravity changes first showed as a gradient zone consistent with the strike of seismogenic fault, and then subsequently exhibited a four-quadrant distribution around the epicentral regions. The earthquakes occurred near the centres of the four-quadrant change and the zero isoline of gravity change. In summary, the gravity data reflected both earthquakes well. The findings indicate that such four-quadrant distributions and gravity change high-gradient zone may be precursor information of earthquake preparation. The results of this study provide a reference for future earthquake monitoring and prediction, with implications for earthquake hazard assessment.